Associations among play, gesture and early spoken language acquisition. Issue 3 (June 2013) - Hall, Suzanne; Rumney, Lisa; Holler, Judith; Kidd, Evan
The present study investigated the developmental interrelationships between play, gesture use and spoken language development in children aged 18–31 months. The children completed two tasks: (i) a structured measure of pretend (or 'symbolic') play and (ii) a measure of vocabulary knowledge in which children have been shown to gesture. Additionally, their productive spoken language knowledge was measured via parental report. The results indicated that symbolic play is positively associated with children's gesture use, which in turn is positively associated with spoken language knowledge over and above the influence of age. The tripartite relationship between gesture, play and language development is discussed with reference to current developmental theory.